2015
DOI: 10.1007/s10903-015-0258-1
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and Self-Rated Mental Health Among Latino and Asian Immigrants in the United States: A Latent Class Analysis

Abstract: This study assesses variations in acculturation experiences by identifying distinct acculturation classes, and investigates the role of these acculturation classes for self-rated mental health among Latino and Asian immigrants in the United States. Using 2002-2003 the National Latino and Asian American Study, Latent Class Analysis is used to capture variations in immigrant classes (recent arrivals, separated, bicultural and assimilated), and OLS regressions are used to assess the link between acculturation cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 87 publications
0
24
1
Order By: Relevance
“…However, these traditional methods of dividing scores are not uniform and therefore subjective, so the comparison of classification results between different studies is almost impossible. To avoid the subjectivity of classification, latent class analysis (LCA) has been increasingly performed to explore variations in cross-cultural adaptation experiences and to identify different adaptation classes [39][40][41]. LCA is a technique used to classify observations based on patterns of categorical responses.…”
Section: Studies On Measurement Of Sociocultural Adaptationmentioning
confidence: 99%
“…However, these traditional methods of dividing scores are not uniform and therefore subjective, so the comparison of classification results between different studies is almost impossible. To avoid the subjectivity of classification, latent class analysis (LCA) has been increasingly performed to explore variations in cross-cultural adaptation experiences and to identify different adaptation classes [39][40][41]. LCA is a technique used to classify observations based on patterns of categorical responses.…”
Section: Studies On Measurement Of Sociocultural Adaptationmentioning
confidence: 99%
“…Language is another source of acculturative stress, as individuals may be excluded from participation in the broader society or unable to understand cultural practices due to inability to speak English. This relationship was found by Bulut and Gayman (), who used latent class analysis to identify patterns of acculturation among Asian and Latino immigrants. Their “separated” class was composed of immigrants who did not speak English and had the lowest self‐rated mental health whereas their “assimilated” class included individuals more likely to speak English and had the highest self‐rated mental health.…”
Section: Introductionmentioning
confidence: 56%
“…Having a strong sense of ethnic identity has been associated with self-efficacy and positive coping, feelings of belonging, and is thought to be protective of adverse mental health functioning 31 , which may support the development of PTG. Previous work by Berry identified distinctstrategies that contribute to individuals’ acculturative typologies such that they may assimilate (adopt the dominant culture and distance from the culture of origin), separate (the opposite of assimilate), integrate (embrace both cultures) or be marginalized (lose all cultural affiliation) 10 .Though this method of categorization has been debated, various studies have verified the existence of these categories in unique samples and have found that those who integrate tend to have more positive health outcomes such as increased mental health, self-esteem and coping-efficacy 25 , supporting our findings.Future research should examine other culturallyinformed beliefs such as support seeking and perceptions of disease (e.g., fatalism) which could also impact growth and wellbeing in the aftermath of a traumatic health event 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Language in which survey was completed was not included as a covariate because only 6 participants completed the survey in Spanish. The dependent variable was PTG (ordinal categories determined by quartiles), and independent variables included ethnicity, RSA, and the Hispanic and Anglo acculturation subscales.The interaction of Hispanic and Anglo orientation was alsotested to explorethe joint effect on PTG, given that biculturalism (high Hispanic orientation and high Anglo orientation) has been associated with health outcomes 25 .In order to provide meaningful and interpretable results, we estimatedprobabilities of reportingthe highest quartile PTG score (scores ≥ 44) for variables that were significant at the p<0.05 level, which were calculatedusing the estimates from each multivariable analysis by simulation using 1000 randomly drawn sets of estimates from a sampling distribution with the mean equal to maximum likelihood point estimates, variance equal to the variance-covariance matrix of the estimates, and covariates setat their mean values 26 . Listwise deletion resulted in 21 missing across all variables for a total sample size of 214 in the multivariable model including all subjects and 112 in the Hispanic-only model.…”
Section: Methodsmentioning
confidence: 99%